Empowerment of Women Fishermen Through Seaweed Agroindustry Business in South Batu Nampar Village, East Lombok Regency - Syarif Husni; Karnan; Didik Santoso; I Gusti Ngurah Aryawan Asasandi (Yayasan Siti Widhatul Faeha, 2026)
The low added value of seaweed remains a major challenge in improving the economic welfare of coastal communities. This community service program aims to strengthen women fisherfolk groups as sustainable business units while enhancing their knowledge and skills in processing seaweed into value-added products. The program was implemented using a participatory empowerment approach that positioned women fisherfolk as the main actors in the activities, including training, group formation, and practical processing sessions. The results show that five women fisherfolk groups were successfully established, each consisting of 10–11 members, indicating the effectiveness of a community-based institutional approach in strengthening local participation. In addition, participants demonstrated increased knowledge and practical skills in processing seaweed into potential economic products. Overall, the seaweed processing training program represents an important initial step in building the foundation of a women-based village agro-industry. These findings suggest that the sustainability of the program depends on continuous mentoring, consistent production, strengthened business management, and the development of sustainable market access to ensure long-term economic benefits for coastal communities.